The Effect of Proactive Personality, Professionalism, and Work Engagement on Performance among Village Midwives in Neonatal Complication Management Using the Integrated Management of Childhood Illness - Farouk Ilmid Davik1 , Fitri Widyacahya1 , Muhammad Ardian Cahya Laksana2 , Nyoman Anita Damayanti1, (Institute of Medico-legal Publications Pvt Ltd, 2020)
Approximately 15% of newborns grow with neonatal complications. The percentage of neonatalcomplications in Probolinggo from 2015 to 2017 has not reached the target of 80%. The number of neonatalcomplications still achieved 68.68% of the minimum service standards target.This study analyzed the effect of proactive personality, professionalism, and work engagement onperformance among village midwives in managing neonatal complications by using an integrated strategymanagement of childhood illness. Proportional random sampling was in use to collect 180 village midwivesas the sample. The research was conducted in Probolinggo Primary Healthcare Center, Indonesia fromMarch to May 2018. The data collected through questionnaires were analyzed with a linear regression.The results showed proactive personality influenced work engagement (p = 0.00). The higher the villagemidwives’ proactive personality is, the higher the level of work engagement is. Besides, professionalisminfluenced performance (p = 0.01). The higher the level of professionalism is, the higher the level ofperformance is. This study also revealed work engagement influenced performance (p = 0.00). The higherthe level of work engagement is, the higher the level of performance is. However, proactive personality didnot affect performance.